An S188V mutation alters substrate specificity of non-stereospecific α-haloalkanoic acid dehalogenase E (DehE) - Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Wahab, Roswanira; Shamsir, Mohd Shahir; Huyop, Fahrul Zaman (The Public Library of Science (PLoS), 2015)
The non-stereospecific α-haloalkanoic acid dehalogenase E (DehE) degrades many halo- genated compounds but is ineffective against β-halogenated compounds such as 3- chloropropionic acid (3CP). Using molecular dynamics (MD) simulations and site-directed mutagenesis we show here that introducing the mutation S188V into DehE improves sub- strate specificity towards 3CP. MD simulations showed that residues W34, F37, and S188 of DehE were crucial for substrate binding. DehE showed strong binding ability for D-2- chloropropionic acid (D-2CP) and L-2-chloropropionic acid (L-2CP) but less affinity for 3CP. This reduced affinity was attributed to weak hydrogen bonding between 3CP and residue S188, as the carboxylate of 3CP forms rapidly interconverting hydrogen bonds with the backbone amide and side chain hydroxyl group of S188. By replacing S188 with a valine residue, we reduced the inter-molecular distance and stabilised bonding of the carboxylate of 3CP to hydrogens of the substrate-binding residues. Therefore, the S188V can act on 3CP, although its affinity is less strong than for D-2CP and L-2CP as assessed by K m . This successful alteration of DehE substrate specificity may promote the application of protein engineering strategies to other dehalogenases, thereby generating valuable tools for future bioremediation technologies.